Potential Markets for Florida Turmeric - Kevin Athearn; Jonathan Adam Watson; Paul Fisher; Maria Paz Kinslow; Marina Burani-Arouca; Brian Pearson; Celina Gómez (EDIS)
This publication examines the potential markets for turmeric (Curcuma longa) grown in Florida, highlighting opportunities in fresh produce, food and beverage ingredients, and nursery markets. Turmeric, widely used in culinary dishes and wellness products, is primarily consumed in its rhizome form, as a powdered spice. The US fresh produce market for turmeric is largely supplied by imports from countries like India, Fiji, and China, presenting price competition challenges for Florida growers. Florida turmeric producers face strong competition from imports, but by focusing on quality, differentiation, and niche markets, they can enhance profitability.